Characterization of chromosome constitution in three wheat - Thinopyrum intermedium amphiploids revealed frequent rearrangement of alien and wheat chromosomes - Cui, Yu (BMC Plant Biol, 2021)
BACKGROUND: Thinopyrum intermedium (2n = 6x = 42) is an important wild perennial Triticeae species exhibiting many potentially favorable traits for wheat improvement. Wheat-Th. intermedium partial amphiploids serve as a bridge to transfer desirable genes from Th. intermedium into common wheat. RESULTS: Three octoploid Trititrigia accessions (TE261–1, TE266–1, and TE346–1) with good resistances to stripe rust, powdery mildew and aphids were selected from hybrid progenies between Th. intermedium and the common wheat variety ‘Yannong 15’ (YN15). Genomic in situ hybridization (GISH), fluorescence in situ hybridization (FISH) and multicolor GISH (McGISH) analyses demonstrated that the three octoploid Trititrigia possess 42 wheat chromosomes and 14 Th. intermedium chromosomes. The 14 alien (Th. intermedium) chromosomes belong to a mixed genome consisting of J-, J(S)- and St-genome chromosomes rather than a single J, J(S) or St genome. Different types of chromosomal structural variation were also detected in the 1A, 6A, 6B, 2D and 7D chromosomes via FISH, McGISH and molecular marker analysis. The identity of the alien chromosomes and the variationes in the wheat chromosomes in the three Trititrigia octoploids were also different. CONCLUSIONS: The wheat-Th. intermedium partial amphiploids possess 14 alien chromosomes which belong to a mixed genome consisting of J-, J(S)- and St- chromosomes, and 42 wheat chromosomes with different structural variations. These accessions could be used as genetic resources in wheat breeding for the transfer of disease and pest resistance genes from Th. intermedium to common wheat. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12870-021-02896-9.